2022
DOI: 10.1002/jsfa.11758
|View full text |Cite
|
Sign up to set email alerts
|

Dietary live yeast supplementation alleviates transport‐stress‐impaired meat quality of broilers through maintaining muscle energy metabolism and antioxidant status

Abstract: BACKGROUND This experiment was to investigate the effect of dietary live yeast (LY, 1 × 1010 CFU g−1) supplementation on serum metabolic parameters, meat quality as well as antioxidant enzyme activity of transported broilers. A total of 192 one‐day‐old broilers were randomly assigned to four treatments with six replicates and eight chicks per replicate: a basal diet without transportation (CON), a basal diet containing 0 (T), 500 (T + LY500) and 1000 mg kg−1 (T + LY1000) LY with 3 h of transportation after fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(139 reference statements)
2
2
0
Order By: Relevance
“…In addition, the transportation time and distance often lead to different levels of body weight loss [ 19 ]. Our study showed that the 3 h transportation treatment increased the body weight loss of broilers, which is consistent with previous studies [ 5 , 20 ]. Meanwhile, dietary SeCe supplementation alleviated the body weight loss of broilers under transportation stress.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the transportation time and distance often lead to different levels of body weight loss [ 19 ]. Our study showed that the 3 h transportation treatment increased the body weight loss of broilers, which is consistent with previous studies [ 5 , 20 ]. Meanwhile, dietary SeCe supplementation alleviated the body weight loss of broilers under transportation stress.…”
Section: Resultssupporting
confidence: 93%
“…According to Pan et al (2018), damage to muscle cells due to decreased pH can increase drip loss and oxidation, which changes the color of the meat. It is in line with He et al (2022) opinion that lower meat pH causes actin and myosin in muscles to condense and contract into granules, destroys a spatial structure, reduces water-holding capacity, and has a direct impact on meat color. Therefore, oxidation which changes the condition of the red meat pigment to yellowish, can occur.…”
Section: Yellownesssupporting
confidence: 86%
“…Myofibrillar reflection contributes to the difference in light scattering between PSE and dark, firm, and dry; this is related to pH, which significantly impacts the clarity of light on the chicken breast and causes the meat to appear pale in parts with a lower pH. Under He et al (2022) opinion, lightness increases with a decrease in the pH value.…”
Section: Lightnessmentioning
confidence: 99%
“…HK, PK, and PFK are the key rate-limiting enzymes involved in the glycolytic metabolism pathway. He et al found that the activities of HK and PK increased significantly in broilers subjected to preslaughter transport. Herein, the activities of HK, PK, and PFK were found to be higher in preslaughter transport-induced PSE-like muscle of broilers.…”
Section: Discussionmentioning
confidence: 99%